Designed Trp/Arg-rich antimicrobial peptides. - Giam, Zhen Gan. (2013)
Researches on Antimicrobial Peptides (AMPs) are fumed by the rise of multidrug resistant (MDR) bacteria. Multiple physiochemical properties are identified to have contributions to antimicrobial activities of these peptides. Based on the information, 5 peptides were designed with the following parameters: helical, short in sequences, contain arginine and tryptophan residues, cationic and high in hydrophobic content that led to amphipathic. Their biological activities and peptides–lipids interactions were investigated. Ultimately, the peptide with the highest positive charge, lowest hydrophobicity and without tryptophan showed greatest potency against the tested bacteria. While 3 other peptides mainly showed comparable, but slightly lowered antimicrobial activities. Cationicity and hydrophobicity are important for initial peptides–membranes bindings, but increasing of these factors was not shown to increase their initial binding or antimicrobial effects. Specific amino acids like Arg and Trp might not be necessary for bindings and activities, in the case of potential helical peptides. Also, AMPs’ higher ability to bind to the membrane might not equate to better ability to kill bacteria.